How to Develop Useful Models for Solid-State Batteries – A Plea for Simplicity and Interdisciplinary Cooperation - Bielefeld, Anja; Justus Liebig University Giessen (My University, 2023)
With research on solid-state batteries being on the rise, also simulations and modeling studies become more and more popular. It is therefore time to reflect upon the interplay of experiments and simulations and the upcoming dilemma of drawing general conclusions from increasingly complex model approaches that naturally go along with advancements and insights in the research field. Albeit this perspective focuses on (microstructure) models for composite cathodes, it is also an invitation to contemplate the epistemological considerations and the proposed tentative agenda on how to build useful models for other sub-fields of the solid-state research community.
Keywords: ddc:540